Mycobacterium avium Infection of Multinucleated Giant Cells Reveals Association of Bacterial Survival to Autophagy and Cholesterol Utilization - Jayanthi J. Joseph; Amy Leestemaker-Palmer; Soheila Kazemi; Lia Danelishvili; Luiz E. Bermudez (Cellular Microbiology)
Mycobacterium avium subsp. hominissuis (M. avium) is an opportunistic environmental pathogen that typically infects patients with existing lung conditions such as cystic fibrosis or COPD. Pulmonary M. avium infection generates peribronchial granulomas that contain infected macrophages and multinucleated giant cells (MGCs). While granuloma formation with MGCs is a common feature of mycobacterial infection, the role of MGCs within the granulomas as well as in the host-pathogen interaction is poorly understood. To shed light on the role of MGCs, we established a novel in vitro model utilizing THP-1 cells stimulated with a combination of IFN-γ and TNF-α. In this study, we show that MGCs can take up M. avium, which replicates intracellularly before leaving the cell. Bacteria that escape the MGC exhibit a highly invasive phenotype, which warrants further evaluation. Characterization of MGCs with transmission electron microscopy revealed an accumulation of cytoplasmic lipid droplets, autophagic activity, and multiple nuclei. Autophagy markers are upregulated in both uninfected and infected MGCs early in infection, measured by RT-qPCR analysis of Beclin-1 and LC3. Inhibition of autophagy with siRNA significantly reduced M. avium survival significantly in THP-1 macrophages. Depletion of host cholesterol and sphingomyelin in MGCs also resulted in decreased survival of M. avium. These processes potentially contribute to the formation of a supportive intracellular environment for the pathogen. Collectively, our results suggest that M. avium is adapted to replicate in MGCs and utilize them as a springboard for local spread.